POLICY FOR THE IMPLEMENTATION OF LARGE-SCALE SOCIAL RESTRICTIONS ON THE ERADICATION OF THE COVID-19 VIRUS IN JAKARTA - Himsar Silaban (Moestopo International Review on Social, Humanities, and Sciences, 2021)
The presence of the Covid 19 Pandemic has ravaged various aspects of human life in the world, including in Indonesia, including: health aspects, economic aspects, education aspects, social aspects, defense and security aspects, cultural aspects, and so on, thus requiring super strict handling. . The purpose of this study was to determine the implementation of the Large-Scale Social Restriction (PSBB) policy towards eradicating the Covid-19 virus in DKI Jakarta. Methods This research uses a qualitative descriptive method. Qualitative research data were collected through in-depth interviews. The results of the analysis of the Large-Scale Social Restrictions (PSBB) policy have not been fully effective in terms of suppressing the transmission of Covid-19 in DKI Jakarta. The standard implementation of DKI Jakarta's Large-Scale Social Restrictions (PSBB) policy has not been running according to community expectations. The level of community compliance is felt to be still less visible than the high number of violations that occurred during the PSBB period.